1988
DOI: 10.1038/clpt.1988.73
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of high-dose etoposide

Abstract: The pharmacokinetics of etoposide at doses of 1 gm/m2 to 3 gm/m2 were studied in patients with hematologic malignancies. The noncompartmental systemic clearance, mean residence time, steady-state volume of distribution, and elimination half-life were independent of the dose of etoposide, whereas the AUC was proportional to the dose. Comparison of these results with those reported previously indicates that etoposide exhibits linear pharmacokinetics over a thirtyfold range in doses (0.1 to 3 gm/m2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Pharmacokinetics of etoposide have been reported to be dose-linear (Hande et al 1984;Newman et al 1988;Slevin 1991;Köhl et al 1992;Würthwein and Boos 2001). To date, however, the relationship between the pharmacokinetic parameters of etoposide and drug dose has been compiled by comparing the data generated from different patient groups who were treated with different dose levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pharmacokinetics of etoposide have been reported to be dose-linear (Hande et al 1984;Newman et al 1988;Slevin 1991;Köhl et al 1992;Würthwein and Boos 2001). To date, however, the relationship between the pharmacokinetic parameters of etoposide and drug dose has been compiled by comparing the data generated from different patient groups who were treated with different dose levels.…”
Section: Discussionmentioning
confidence: 96%
“…In effect, etoposide is one of the major nonalkylating agents in current use for high-dose chemotherapy (Jones et al 1995). Pharmacokinetics of etoposide have been reported to be dose-linear (Hande et al 1984;Newman et al 1988;Slevin 1991;Köhl et al 1992;Würthwein and Boos 2001). So far, the relationship between drug dose and pharmacokinetic parameters has been established by use of the data generated from different populations who were treated with varying doses, while an intraindividual comparison (which has the advantage of excluding the problem of between-patient variability as a confounding factor) has not yet been performed.…”
Section: Introductionmentioning
confidence: 97%
“…We used etoposide phosphate, as it is widely used in oncology and hematology, often with dose intensification. Furthermore, etoposide, which is used over a wide range of dosages, has been shown to have a half-life independent of dosage and an area under the curve (AUC) proportional to the dose (8). The dosage in connection with stem cell transplantation is equivalent to 30-40 mg/kg but is given in combination with intensive doses of three other cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide is a semisynthetic derivative of podophyilotoxin and has proven activity in both myeloid and lymphoid malignancies including efficacy in standard doses in relapsed haematologic disease [22-241 and in high doses followed by marrow rescue [9,. It demonstrates linear pharmacokinetics [29] and penetrates the CSF after high-dose intravenous administration [30]. Phase 1 and 2 studies have shown dose-limiting toxicity at 50-70 mg/kg ideal body weight [31,32].…”
Section: Discussionmentioning
confidence: 99%